International Students’ Consciousness of Postgraduate Programmes of Learning in the UK (مجلة البحوث الأكاديمية, 2022)
Students from all parts of the world come to the UK every year to pursue courses in higher education. The purpose of this study is to investigate the impressions international students (N=80) obtained and developed after spending some time at British universities. The study was guided by two research questions: (1) What is the students’ attitude of the postgraduate programme they are currently undertaking? (2) What are the problems that overseas students face while studying in the UK? Moreover, the study explored the problems that these students experienced while studying in the UK. The researchers used three tools to obtain the data needed, namely nominal group technique, interviews and questionnaires. The findings in the current study revealed that students pursue their postgraduate studies because they had limited chances in their countries of origin. Besides, students were encountered by various difficulties and problems.
Keywords: international students; postgraduate programme; the UK; attitude